Ukrainian banks and increasing their competitiveness in the international market - Murlyk, Anastasiya (My University, 2014)
This work represents modem method of control over the banking services provided by the Ukrainian banks to foreign customers which is widespread and popular in the international practice.
Keywords: Ukrainian banks; competitiveness; international market; українські банки; конкурентоспроможність; міжнародний ринок; украинские банки; конкурентоспособность; международный рынок